Type I Interferons Direct Gammaherpesvirus Host Colonization - Tan, Cindy S. E. (PLoS Pathog, 2016)
Gamma-herpesviruses colonise lymphocytes. Murid Herpesvirus-4 (MuHV-4) infects B cells via epithelial to myeloid to lymphoid transfer. This indirect route entails exposure to host defences, and type I interferons (IFN-I) limit infection while viral evasion promotes it. To understand how IFN-I and its evasion both control infection outcomes, we used Mx1-cre mice to tag floxed viral genomes in IFN-I responding cells. Epithelial-derived MuHV-4 showed low IFN-I exposure, and neither disrupting viral evasion nor blocking IFN-I signalling markedly affected acute viral replication in the lungs. Maximising IFN-I induction with poly(I:C) increased virus tagging in lung macrophages, but the tagged virus spread poorly. Lymphoid-derived MuHV-4 showed contrastingly high IFN-I exposure. This occurred mainly in B cells. IFN-I induction increased tagging without reducing viral loads; disrupting viral evasion caused marked attenuation; and blocking IFN-I signalling opened up new lytic spread between macrophages. Thus, the impact of IFN-I on viral replication was strongly cell type-dependent: epithelial infection induced little response; IFN-I largely suppressed macrophage infection; and viral evasion allowed passage through B cells despite IFN-I responses. As a result, IFN-I and its evasion promoted a switch in infection from acutely lytic in myeloid cells to chronically latent in B cells. Murine cytomegalovirus also showed a capacity to pass through IFN-I-responding cells, arguing that this is a core feature of herpesvirus host colonization.